1917 N.C. Sess. Laws 309, Pub.-Local Laws, ch. 209, § 1 - (:unkn) unknown (General Publisher, 1917)
Prohibited killing quail with a gun that shoots over two times before reloading.
--
Keywords: HUNTING REGULATION